Predictors of children's secondhand smoke exposure at home: a systematic review and narrative synthesis of the evidence - Orton, Sophie; Jones, Laura L.; Cooper, Sue; Lewis, Sarah; Coleman, Tim (Public Library of Science, 2014)
BACKGROUND: Children's exposure to secondhand smoke (SHS) has been causally linked to a number of childhood morbidities and mortalities. Over 50% of UK children whose parents are smokers are regularly exposed to SHS at home. No previous review has identified the factors associated with children's SHS exposure in the home.